"The Only Industry That Can Make Us Hold Our Own": Black Agrarianism in South Africa from a Transatlantic Perspective, ca. 1910–1930. Issue 4 (18th December 2021) - Tischler, Julia
Abstract: By exploring agricultural education initiatives in South Africa in the period from the 1910s to the 1930s, this article seeks to expand the historiography of both Black internationalism and global progressivism to include Black agrarianism and questions of race from a transatlantic perspective. In their efforts to promote scientific farming, Black progressive farmers in the Eastern Cape reserves made strategic use of the famous educational philosophy of the Tuskegee Institute in Alabama as an enabling discourse that allowed them to gain an audience for their specific, localized claims to economic and political participation in a segregationist country. While the existing historiography has discussed Tuskegee's impact in Africa as an example of oppressive labor education, this article argues that Black agrarian progressivism should be taken seriously as a form of antiracism and Pan-Africanism, albeit one that was classist and patriarchal.